Respuesta :

The only error you made is on problem 3. Everything else is correct. Nice work.

-------------------------------------------------------

Here is how to solve problem 3

Plug x = 1 into the equation and solve for y

-3x + y = 1

-3*1 + y = 1 ... replace x with 1

-3 + y = 1

y - 3 = 1

y - 3 + 3 = 1 + 3 .... add 3 to both sides

y = 4

The answer is 4

-------------------------------------------------------

Verifying the answer:

Plug (x,y) = (1,4) into the equation. Both sides should be the same number after simplifying both sides.

-3x + y = 1

-3*1 + 4 = 1 ..... replace x with 1; replace y with 4

-3 + 4 = 1

1 = 1

The answer is confirmed.

If you were to graph -3x + y = 1, which is equivalent to y = 3x+1, you'll find that the point (1,4) is on this line.